Regional Contracts in the Polish Development Policy - Churski, Paweł (Quaestiones Geographicae, 2018)
Regional contracts developed in Poland as a consequence of the process of the state decentralisation and the building of local governments in the 1990s. By learning from other countries’ experiences (especially the French regional policy), an instrument was devised in order to support the decentralisation of the state development intervention and to foster the regions’ empowerment to programme and administer the regional policy. Unfortunately, since the very first edition, regional contracts in Poland have become a hostage to impromptu political acts determining changes to the economic policy, the limited state budget and very frequent legal amendments. The goal of this article is to conduct a synthetic analysis of the origins, changes and challenges related to the use of regional contracts in the Polish development policy. The author’s subjective, critical opinions were confronted with the opinions of the representatives of regional authorities in selected voivodeships. To this end, interviews were conducted with directors of departments in selected marshal offices. The resulting evaluation, conclusions and recommendations allowed the verification of the author’s subjective views.